1996
DOI: 10.1073/pnas.93.4.1619
|View full text |Cite
|
Sign up to set email alerts
|

Persistent elevations of cerebrospinal fluid concentrations of corticotropin-releasing factor in adult nonhuman primates exposed to early-life stressors: implications for the pathophysiology of mood and anxiety disorders.

Abstract: There is increasing evidence for an important role of adverse early experience on the development of major psychiatric disorders in adulthood. Corticotropinreleasing factor (CRF), an endogenous neuropeptide, is the primary physiological regulator of the mammalian stress response. Grown nonhuman primates who were exposed as infants to adverse early rearing conditions were studied to determine if long-term alterations of CRF neuronal systems had occurred following the early stressor. In comparison to monkeys rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
370
3
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(403 citation statements)
references
References 26 publications
26
370
3
2
Order By: Relevance
“…Similarly, Heim et al [18] found that severe stress (sexual and physical abuse) early in life is associated with persistent sensitization of the HPA axis, which in turn is related to an increased risk for adulthood psychopathological conditions. These findings are consistent with results from several animal studies [8,28]. De Bellis [12] considered feelings of neglect or reports of having been neglected during childhood and adolescence as reflecting a chronic stressor that causes anxiety-and depressive disorders during child and/or adulthood, and most likely, a dysregulation of the biological stress system.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Heim et al [18] found that severe stress (sexual and physical abuse) early in life is associated with persistent sensitization of the HPA axis, which in turn is related to an increased risk for adulthood psychopathological conditions. These findings are consistent with results from several animal studies [8,28]. De Bellis [12] considered feelings of neglect or reports of having been neglected during childhood and adolescence as reflecting a chronic stressor that causes anxiety-and depressive disorders during child and/or adulthood, and most likely, a dysregulation of the biological stress system.…”
Section: Discussionsupporting
confidence: 87%
“…The effect exerted by maternal deprivation resulted in the altered expression of the hippocampal mineralo (MR) and glucocorticoid receptor (GR) sites (Oitzl et al, 2000) in a manner that would explain the enhanced HPA responsiveness (De Kloet et al, 1998). In other studies, early stress was found to induce an increase in the number of hypothalamic CRH neurons and an increase in CRH and AVP m-RNA expression (Coplan et al, 1996(Coplan et al, , 2001De Goeij et al, 1992;Hatalski et al, 1998;Lim, 2000;Plotsky and Meaney, 1993). An elevated AVP/CRH release is likely to enhance the expression of pro-opiomelanocortin (POMC) synthesis and the release of its peptide product ACTH in the pituitary corticotrophs.…”
Section: Discussionmentioning
confidence: 97%
“…(Heim et al, 2000a, b). Clinical and preclinical studies suggest that an enhanced expression of CRH and its potent coregulator arginine vasopressin (AVP) in the hypothalamic nucleus paraventricularis (PVN) is involved in the pathogenesis of this hyper-responsiveness of the HPA axis (Coplan et al, 1996;Hatalski et al, 1998;von Bardeleben et al, 1985). This hyper-responsiveness of the HPA axis may render the abused BPD patients very susceptible to stress, and in case of sustained stress to depression comparable with subjects with a heritable predisposition for MDD .…”
Section: Introductionmentioning
confidence: 99%
“…Both animal and human studies indicate that chronic or severe stress exposure, especially early in life (Coplan et al, 1996), can result in persistent alterations in neurobiological systems that are stress responsive (Bremner & Vermetten, 2001;Heim et al, 2001). There is particularly compelling evidence that such long-term adaptation to either early life stress or to chronic on-going stress occurs for HPA axis regulation (Lemieux & Coe, 1995;Resnick et al, 1995;Coplan et al, 1996;Ladd et al, 1996;Kaufman et al, 1997, Heim et al, 2001Szikszay & Benedek, 1989;D'Amore et al, 1993;Heim et al, 2002;Bennett et al, 2004), and there is also evidence that it occurs for noradrenergic regulation (Bremner et al, 1996;Young & Breslau, 2004).…”
Section: Stress Dysregulation In Neuroactive Steroids: Implications Fmentioning
confidence: 99%